Fao Report on Biodiversity for Food and Agriculture. (1st April 2019) - Unknown
FAO has a long history of fostering sustainable agricultural development and the sustainable use of biodiversity for food and agriculture to pursue its goal of ending poverty and hunger; Based on information provided by 91 countries and 27 international organizations, analysis of global literature and datasets, and contributions from over 175 authors and reviewers, The State of the World?s Biodiversity for Food and Agriculture assesses biodiversity for food and agriculture and its management worldwide.